Ethical analysis of unsafe abortion cases in the Philippines - Sarmiento, Jia Angelu P. (Animo Repository, 2024)
The Philippines prohibits abortion without any exceptions under the Philippines’ 1987 Constitution of the Republic of the Philippines, Article II, Section 12, and the Revised Penal Code of the Philippines, Act. No. 3815 of December 8, 1930, Articles 256 – 259. This has pushed women to undergo illegal abortion due to pregnancies caused by rape and incest, present health risks, fetal impairment, financial incapability, and bodily autonomy. Filipino women enter into an unsafe process of abortion over a wide range of methods and that includes surgery or “operation”, abortive pills such as Misoprostol, hormonal pills, injectable hormonal contraceptive, insertion of a catheter into the cervix, insertion of other objects into the cervix, massage, aspirin or other related medications, eating or drinking traditional medicine or herbs, drinking alcohol, fasting, climbing a tree, jumping, and exercising. This paper presents two cases of unsafe abortion in the Philippines: one resulted in the death of the mother and one resulted in successful abortion in pursuit of answering the question. I utilize Hare’s two-level utilitarinism as an attempt to provide a direct answer pertaining to which action is morally right or wrong on the issue of unsafe abortion. Although the application of Hare’s two-level utilitarianism to the presented cases showed the failure to guarantee universalizability, prescription, and preference of unsafe abortion, in the end, I failed on the attempt of providing a direct answer to the moral dilemma brought by unsafe abortion due to the conflicting considerations that arise in approaching the issue.